Analysis of Consumer Preferences and Satisfaction with Local Chicken Meat in Bandung City Traditional Markets (Survey of Consumers at Cibogo Market, Sukajadi) - Judanto, Irgo Bintang; Arief, Hasni; Daud, Andre Rivanda (Jurnal Peternakan, 2024)
ABSTRACT.  The demand for local chicken meat in Bandung city has been decreasing over the last five years. Changes in demand for a product can be influenced by consumer preferences and satisfaction. This research was conducted to determine consumer preferences based on the attributes inherent in local chicken meat and the level of consumer satisfaction with local chicken meat. The research location was at Cibogo Market, Sukajadi District, Bandung City. Primary data was obtained from interviews with 97 local chicken meat consumers (as respondents) and secondary data was from the journals and articles research, internet, and related instance. The data analysis method used is Importance Performance Analysis (IPA) to determine preferences and Customer Satisfaction Index (CSI) to determine the level of consumer satisfaction. The results of the research showed that consumer preferences for local chicken meat at Cibogo Market are based on attributes that are included in the main priority class, namely meat tenderness, age, and weight of local chicken. The result of CSI calculation was 71.61% which means that consumers are satisfied. In conclusion, the performance of attributes that are a priority for consumers need to be improved in terms to increase consumer satisfaction to a very satisfied level.